Brought to light: III. Colors of disk and clump substructures in dwarf early-type galaxies of the Fornax cluster - Michea, Josefina; Pasquali, Anna; Smith, Rory; Calderón-Castillo, Paula; Grebel, Eva K.; Peletier, Reynier F. (The astronomical journal, 2022)
It has been well established that dwarf early-type galaxies (ETGs) can often exhibit a complex morphology, whereby faint spiral arms, bars, edge-on disks, or clumps are embedded in their main, brighter diffuse body. In our first paper (“Brought to Light I”), we developed a new method for robustly identifying and extracting substructures in deep imaging data of dwarf ETGs in the Virgo galaxy cluster. Here we apply our method to a sample of 23 dwarf ETGs in the Fornax galaxy cluster, out of which 9 have disk-like and 14 have clump-like substructures. According to Fornax Deep Survey (FDS) data, our sample constitutes 12% of all dwarf ETGs in Fornax brighter than M r = − 13 mag, and contains all cases that unequivocally exhibit substructure features. We use g- and r-band FDS images to measure the relative contribution of the substructures to the total galaxy light and to estimate their g − r colors. We find that the substructures typically contribute 8.7% and 5.3% of the total galaxy light in the g and r bands, respectively, within two effective radii. Disk substructures are usually found in dwarf ETGs with redder global colors, and they can be either as red as or bluer than their galaxy’s diffuse component. In contrast, the clump substructures are found in comparatively bluer dwarf ETGs, and they are always bluer than their galaxy’s diffuse component. These results provide further evidence that dwarf ETGs can hide diverse complex substructures, with stellar populations that can greatly differ from those of the dominant diffuse light in which they are embedded.
Gesehen am 08.07.2022